Immigrants in Québec: Toward an Explanation of How Multiple and Potentially Conflictual Linguistic Identities Become Integrated - Amiot, Catherine; de la Sablonnière, Roxane (Diversité urbaine, 2008)
AbstractThe aim of this paper is to apply a newly developed theoretical model to the understanding of how a new linguistic identity becomes integrated in immigrants’ self-concept. While intergroup theories have addressed the situational changes in social identities, the longer-term processes underlying developmental changes in identities and their integration within the self remain to be identified. Relying on developmental and social cognitive principles, we aim to explain the specific processes by which a new linguistic identity develops and becomes integrated within the self over time. We focus on the particular situation of new immigrants in Québec who need to integrate new linguistic identities (French, English). The social factors that facilitate versus impede these change processes and the consequences associated with the integration of a new linguistic identity are also discussed.